Quelques emprunts du gallo au breton - Jean-Paul Chauveau (La Bretagne Linguistique, 1985)
We would like to draw from the lexemes that Welsh has borrowed from Breton an image of the relationships maintained throughout history by the two linguistic communities between which Brittany is divided. The presentation focuses on a few examples: "earthworm", "bilberries", "beehive", "reed", "ram" and "the last furrow at the end of a field". The aim here is to highlight the borrowing process itself in the borrowed forms, i.e. the transposition from one linguistic system to another. In this way, we can gain a better understanding of the linguistic history of this former mixed zone.